Impact of transient and chronic loneliness on progression and reversion of frailty in community-dwelling older adults: four-year follow-up - Chu, Bin-Lin; Zhang, Wen (BMC geriatrics, 2022)
Frailty is a common condition in older adults that is characterized by transitions between frailty states in both directions (progression and reversion) over time. Loneliness has been reported to be associated with the incidence of frailty, but few studies have explored the impact of persistent loneliness over time on frailty. In this study, we aimed to whether and how two different types of loneliness, transient and chronic, were associated with changes in frailty status in older adults. The analytic sample contained 2961 adults aged ≥ 60 years who completed interviews for both the 2011 and 2015 waves of the China Health and Retirement Longitudinal Study. The logistic regression model was used to examine the relationship between transient and chronic loneliness and progression and reversion of frailty. Demographics (age, sex, education level, marital status, urban-rural residence), living alone, chronic conditions, physical function, and depressive symptoms from the 2011 wave were adjusted. After four years, 21% of the studied sample reported progression, 20% reported reversion in frailty, 31% reported transient loneliness, and 14% reported chronic loneliness. There was no significant difference in participants who reported transient loneliness (OR = 1.10, 95% CI [0.89,1.37]), or chronic loneliness (OR = 1.14, 95% CI [0.84,1.57]) on the progression of frailty, compared with no report of loneliness. Participants reporting chronic loneliness (OR = 0.68, 95% CI [0.50,0.93]) were less likely to report reversion in their level of frailty compared to participants who did not report loneliness but not transient loneliness (OR = 0.87, 95% CI [0.70,1.08]). Roughly the same percentage, a fifth, of older Chinese adults progressed or reversed in frailty status without active intervention. Chronic loneliness was related to a lower probability of reversion in the frail group than in the no loneliness group, but not in the transient loneliness group. More attention should be given to older adults with chronic loneliness.